Analysis of the field monitoring data on soil movements and adjacent building settlement due to shield tunnelling. Issue 4 (13th May 2019) - Ding, Zhi; Wei, Xinjiang; Zhang, Xiao; Yin, Xinsheng
Abstract : Purpose: The shield tunnels closely constructed near the foundations have an inevitable influence on the structures, even results in the large settlement or uplift of the structures. Design/methodology/approach: The comparison of structural deformation of three different foundations is presented based on the field monitoring data. Findings: Shield tunnelling parameters vary for the different types of foundations. For the long pile foundations, the recommended speed is 3 to 4 cm/min, the grouting pressure is about 0.3 MPa and the grouting rate ranges from 150 to 180. Originality/value: The study based on the field monitoring data is rarely reported, especially the topic about the structural deformation of different types of the foundations.